PERANCANGAN APLIKASI SISTEM INVENTORY BARANG MENGGUNAKAN BARCODE SCANNER BERBASIS ANDROID - Putra Yudha, I Putu Alit; Sudarma, Made; Arya Mertasana, Putu (Jurnal SPEKTRUM, 2018)
This research aims to design an applications of goods inventory system that uses barcode scanner on Android device. The desktop applications is based on Basic language and on for Android applications is developed using Java language. MySql database is store on online server, so that can be accessed by applications in Android mobile. The process of data exchange between Android and database is done by using web service to make distribution data easier.The result of making the application that is able to check the information status of goods stock availability via Android smartphone just by scanning the barcode listed on the goods. Indirectly this application can also increase the waiter’s service to the consumers.